International medical support for disaster relief: From the standpoint of Japan Medical Team for Disaster Relief - Fuke, Nobuo (Japanese Journal of Reanimatology, 1997)
Japan Medical Team for Disaster Relief (JMTDR) is a volunteer-based medical team organized to offer medical service for disaster victims abroad. The team was established in 1982 as a part of Japan Disaster Relief (JDR), which consists of rescue, medical and rehabilitation (life line reconstruction) teams, and is a kind of govermental organization under the control of Japan International Cooperation Agency (JICA) . When it takes action in response to the request of the goverment of the afflicted country, an expeditionary team is picked up from the resistered members; consisting 179 physicians, 216 nurses, and 121 coordinators. The team is dispatched within 24 hours after the request. Since 1982 JMTDR has dispatched its members for 34 times to Asia, Middle East, Africa and other developing areas and offered a good quality of service. In comparison with NGO's, JMTDR as an official organization has the advantage of budget, security, and accessibility to go in and out of a foreign country. Though there are still some problems to be solved like shortening the response time not from the request but from the outbreak of the disaster, JMTDR is one of the most successful organizations to help disaster victims.